2012
DOI: 10.1371/journal.pone.0044341
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence Parental Attitudes toward Enrollment in Type 1 Diabetes Trials

Abstract: AimsTo assess parental attitudes towards type 1 diabetes clinical trials (T1DCTs) and factors that impact willingness to enroll their children with and without diabetes.MethodsA cross-sectional survey of parents of children with type 1 diabetes was administered at an academic clinic and a diabetes educational event.ResultsSurvey response rate was 36%. Of 166 participating parents, 76% were aware of T1DCTs. More parents reported willingness to enroll children with diabetes (47%) than unaffected children (36%). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…Persons with diabetes in our study who were willing to participate expressed concerns about risk and aversion to research—‘the guinea pig fear”—like those that parents of children with diabetes endorsed in a previous study (Buscariollo et al 2012). Regarding positive reasons for enrolling in research, persons with diabetes in our study, like those of Roberts et al (2006) with HIV and thought disorder, affirmed altruism and the growth of scientific knowledge as primary reasons to enter research.…”
Section: Discussionmentioning
confidence: 79%
“…Persons with diabetes in our study who were willing to participate expressed concerns about risk and aversion to research—‘the guinea pig fear”—like those that parents of children with diabetes endorsed in a previous study (Buscariollo et al 2012). Regarding positive reasons for enrolling in research, persons with diabetes in our study, like those of Roberts et al (2006) with HIV and thought disorder, affirmed altruism and the growth of scientific knowledge as primary reasons to enter research.…”
Section: Discussionmentioning
confidence: 79%
“…In the free text area, several respondents commented about time constraints, or the stress of travel with their cat, so inquiring only about the number of trips with or without their cat might not have entirely encompassed concerns regarding travel among the respondents. Transportation issues are a potential hindrance to participation in human clinical trials, 20 particularly for rural populations, 4 and our inclusion of clients at moderately urban hospitals in this study could have decreased this concern among respondents. However, we consider the stress of travel with the cat to be of particular concern to cat owners.…”
Section: Discussionmentioning
confidence: 98%
“…Also, the current trial did not include a placebo arm. One study found about parental attitudes towards enrolment in a Type 1 diabetes trial found that only a minority of parents were comfortable with the possibility of their child being randomised to a placebo arm (35). We did not interview any parents whose baby had died after participation in the trial and it is likely that their perceptions of the trial would have been different (16).…”
Section: Accepted Articlementioning
confidence: 99%